PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL PADA PT. BINA AVIA PERSADA - Pakasi, Devis Lucky (ACCOUNTABILITY, 2015)
Influence of budget participation has attracted the attention of researchers in recent years. Some research on the relationship of budget participation on managerial performance indicates inconsistent results. This study aims to prove the existence and how the influence of budget participation on managerial performance.The object in this research is PT. Avia Bina Persada in the company is engaged in the scope of the airlines that provide short pelatian for prospective flight attendants and staff of the airlines. For the data used in this study was obtained from the perception of employees and corporate leaders involved in the preparation of the budget, including middle managers and ordinary employees lower managers. Data obtained through questionnaires to 20 employees and 10 managers with a total questionnaires were distributed to 30 sheets. The analysis model is a simple linear regression.The result is that the PT. Avia Bina Persada, a positive effect of budget participation on managerial performance. That is, the higher the participation, the budget will be higher the managerial performance.